Strategic dilemmas of pre election marketing in the age of the mediatisation of politics: The case of the Warsaw referendum of 2013 - Kolczyński, Mariusz (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The referendum on the dismissal of the President of Warsaw Hanna Gronkiewicz-Waltz before the end of her term was a part of a series of political events that could affect the power arrangement on the Polish political scene, especially on the market position of the Civic Platform (Platforma Obywatelska) and the Law and Justice (Prawo i Sprawiedliwość) parties. By analysing the actions taken by the main political actors in the pre‑referendum period, two basic issues should be resolved: if political‑market entities actually carry out their long‑term political strategies and whether the adopted strategy translates into a specific and clear marketing concept of pre‑election activities in the prevalent Polish political realm. Regardless, however, of the adopted strategic option, competing political entities should take into account the obvious fact that the mass media are responsible for delimiting the area of political discourse and for defining matters which are a subject thereof. Key words: The Warsaw referendum, mediatisation of politics, political marketing